Comprehensive review of Mycobacterium ulcerans and Buruli ulcer from a bioinformatics perspective – what have we learnt? - Sur, Saubashya; Pal, Biswajit (Acta Biologica Szegediensis, 2022)
Mycobacterium ulcerans is a non-tuberculous mycobacterium responsible for causing Buruli ulcer. This is a neglected tropical disease characterized by ulceration, necrotization and scarring of the soft tissues in human limbs. Pathogenesis of M. ulcerans is mediated by a cytotoxic and immunosuppressive compound called mycolactone. This steadily evolving mycobacteria has adapted itself with the aquatic insect ecosystem. Human communities in wetland ecosystems are prone to Buruli ulcer and several endemic regions have been identified. So far, there is no vaccine and surgery or prolonged treatment with antibiotic cocktail has been mandated to overcome resistance patterns. Application of bioinformatics tools in M. ulcerans and Buruli ulcer research during the post genomic era, has provided immense opportunities. In this review, we summarize the outcome of genome studies, comparative genomics, population genomics, genetic diversity analysis, phylogenetic studies and proteomics research pertaining to this disease. We also highlight the implications of in silico vaccine design and computational studies on natural products. Resultant findings are conducive for interpreting genome architecture, pathogenomic evolution and intraspecific divergence due to phylogeographic and virulence factors of M. ulcerans. Moreover, the outcome of population genomics studies in disease management, coupled with the efforts in discovering vaccine candidates and novel lead compounds, will enrich our understanding of Buruli ulcer.